PENGARUH DESAIN PRODUK DAN FITUR PRODUK TERHADAP LOYALITAS PELANGGAN - Zuhdi, Saefudin; Aprilianto, Rendi (LPPM Institut Bisnis dan Informatika Kesatuan, 2015)
Design Product and Features Product are parts of competitive strategies for business enterprises. Blackberry Smartphone uses the Blackberry Messenger as one of features to recognize the customer needs. Smartphone Blackberry appear with on attractive design. The objective of research is to determine the interest of consumers in product design and its feature. surveys methods uses in research by interviews 100 students in STIE Kesatuan Bogor. Partial Least Square SMART PLS 3.0 software uses to analyze datas. The results of the research consists of: (1) The Product Design has a significant and positive effect to customer loyalty, (2) The Product Features has an insignificant positive effect to costumer loyalty. Furthermore, in order to evaluate the goodness offit the model, the other variables must be used in the next research. Keyword: Product design, product feature